COMPARATIVE ANALYSIS OF NETWORK PERFORMANCE BETWEEN MULTIPROTOCOL LABEL SWITCHING AND SOFTWARE-DEFINED WIDE AREA NETWORK USING QUANTITATIVE EXPERIMENTAL METHODS AT BANK RAKYAT INDONESIA - Ade Suherman; Hani Harafani (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2026)
Bank Rakyat Indonesia’s conventional network infrastructure based on MPLS is considered to have limitations in traffic management flexibility, bandwidth capacity, and operational cost efficiency. Therefore, the implementation of SD-WAN has emerged as a solution to improve network performance and optimize service quality. This study aims to comparatively analyze the network performance of MPLS and SD-WAN using a quantitative experimental approach in the environment of BRI. The research method was conducted by applying specific treatments and testing scenarios, such as bandwidth configuration, traffic load simulation, and failover testing, followed by controlled measurements of Quality of Service parameters, including throughput, latency, jitter, packet loss, and bandwidth utilization. The research data were obtained from the Dashboard MONICA and Portal NSO. The experimental results indicate that the implementation of SD-WAN improves network performance, particularly in maintaining latency and jitter stability, reducing packet loss, and optimizing bandwidth utilization under various operational conditions. Furthermore, the cost analysis reveals potential operational cost efficiency compared to conventional MPLS-based networks. Based on the experimental results and quantitative analysis, it can be concluded that SD-WAN implementation is technically and economically effective in supporting the modernization of data communication network infrastructure at BRI.